Dendritic Cell Responses and Function in Malaria - Yap, Xi Zen; Lundie, Rachel J.; Beeson, James G.; O'Keeffe, Meredith (Frontiers in Immunology, 2019)
Malaria remains a serious threat to global health. Sustained malaria control and, eventually, eradication will only be achieved with a broadly effective malaria vaccine. Yet a fundamental lack of knowledge about how antimalarial immunity is acquired has hindered vaccine development efforts to date. Understanding how malaria-causing parasites modulate the host immune system, specifically dendritic cells (DCs), key initiators of adaptive and vaccine antigen-based immune responses, is vital for effective vaccine design. This review comprehensively summarizes how exposure to Plasmodium spp. impacts human DC function in vivo and in vitro. We have highlighted the heterogeneity of the data observed in these studies, compared and critiqued the models used to generate our current understanding of DC function in malaria, and examined the mechanisms by which Plasmodium spp. mediate these effects. This review highlights potential research directions which could lead to improved efficacy of existing vaccines, and outlines novel targets for next-generation vaccine strategies to target malaria.